Machine Learning Prediction and Recommendation Framework to Support Introductory Programming Course - Khan I.; Ahmad A.R.; Jabeur N.; Mahdi M.N. (International Association of Online Engineering, 2023)
Decision trees; Failure analysis; Forecasting; Machine learning; Predictive analytics; F measure; Failure rate; High-accuracy; Introductory programming; Introductory programming course; Precautionary measures; Prediction model; Students